In-target production of [11C]CH4 from a nitrogen/hydrogen gas target as a function of beam current, irradiation time, and target temperature - Helin, Semi (Springer Nature, 2025)
Background: Production of [11C]CH4 from gas targets is notorious for weak performance with respect to yield, especially when using high beam currents. Post-target conversion of [11C]CO2 to [11C]CH4 is a widely used roundabout method in 11C-radiochemistry, but the added complexity increase the challenge to control carrier carbon. Thus in-target-produced [11C]CH4 is superior with respect to molar activity. We studied the in-target production of [11C]CO2 and [11C]CH4 from nitrogen gas targets as a function of beam current, irradiation time, and target temperature.
Results: [11C]CO2 production was practically unchanged across the range of varied parameters, but the [11C]CH4 yield, presented in terms of saturation yield YSAT(11CH4), had a negative correlation with beam current and a positive correlation with target chamber temperature. A formulated model equation indicates behavior where the [11C]CH4 formation follows a parabolic graph as a function of beam current. The negative square term, i.e., the yield loss, is postulated to arise from Haber-Bosch-like NH3 formation: N2 + 3H2 → 2NH3. The studied conditions suggest that the NH3 (liq.) would be condensed on the target chamber walls, thus depleting the hydrogen reserve needed for the conversion of nascent 11C to [11C]CH4.
Conclusions: [11C]CH4 production can be improved by increasing the target chamber temperature, which is presented in a mathematical formula. Our observations have implications for targetry design (geometry, gas volume and composition, pressure) and irradiation conditions, providing specific knowledge to enhance [11C]CH4 production at high beam currents. Increased [11C]CH4 radioactivity is an obvious benefit in radiosynthesis in terms of product yield and molar radioactivity.